2014
DOI: 10.1128/aac.02338-13
|View full text |Cite
|
Sign up to set email alerts
|

The T2 Mycobacterium tuberculosis Genotype, Predominant in Kampala, Uganda, Shows Negative Correlation with Antituberculosis Drug Resistance

Abstract: e Surveillance of the circulating Mycobacterium tuberculosis complex (MTC) strains in a given locality is important for understanding tuberculosis (TB) epidemiology. We performed molecular epidemiological studies on sputum smear-positive isolates that were collected for anti-TB drug resistance surveillance to establish the variability of MTC lineages with anti-TB drug resistance and HIV infection. Spoligotyping was performed to determine MTC phylogenetic lineages. We compared patients' MTC lineages with drug s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
2
13
0
Order By: Relevance
“…Although response to first-line anti-TB drugs would offer a better explanation to predominance, in this study, we have found no significant differences in the susceptibility patterns between M. tuberculosis Uganda II vs. Beijing or Delhi/CAS families, except at high drug concentrations under oxygen-depleted conditions where the Uganda II family was instead more susceptible to Rifampicin and Isoniazid than the Beijing or Delhi/CAS families. Therefore, in line with recent studies [ 4 – 6 ], the predominance of M. tuberculosis Uganda family in Uganda may not be attributed to its susceptibility behavior once exposed to Isoniazid and Rifampicin.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although response to first-line anti-TB drugs would offer a better explanation to predominance, in this study, we have found no significant differences in the susceptibility patterns between M. tuberculosis Uganda II vs. Beijing or Delhi/CAS families, except at high drug concentrations under oxygen-depleted conditions where the Uganda II family was instead more susceptible to Rifampicin and Isoniazid than the Beijing or Delhi/CAS families. Therefore, in line with recent studies [ 4 – 6 ], the predominance of M. tuberculosis Uganda family in Uganda may not be attributed to its susceptibility behavior once exposed to Isoniazid and Rifampicin.…”
Section: Discussionsupporting
confidence: 80%
“…Chromosomal DNA used as templates in PCRs was prepared as previously described [ 17 ]. Similarly, the M. tuberculosis spoligotypes were determined by Spoligotyping as recently described [ 6 ]. The isolates were re-genotyped using MIRU-VNTR [ 17 ] and SNP-based Real-Time PCR [ 8 ] to confirm that they belong to M. tuberculosis Beijing, Uganda II and Delhi/CAS families.…”
Section: Methodsmentioning
confidence: 99%
“…Different non-Beijing sublineages exhibit diverse correlation with drug susceptibility, even within the same sublineage. A recent study from Lukoye et al has revealed that the T2 MTB genotype is associated with anti-TB drug resistance [36], whereas T2 family strains isolated from Uganda has no statistical relation with anti-TB drug resistance [37]. We hypothesize that this difference is due to the poor discriminatory power of spoligotyping.…”
Section: Discussionmentioning
confidence: 89%
“…Mihret et al [ 19 ] reported a high proportion of T and CAS family strains in Addis Ababa while, Derbew et al [ 20 ] reported a higher prevalence of T family strains in the southern region of Ethiopia. T1 and CAS families have similarly been reported to be frequent in other African countries such as Tanzania and Uganda [ 21 , 22 ]. This indicates a possible broad distribution of these M .…”
Section: Discussionmentioning
confidence: 99%